Western Anti-Judaism Goes East: Syriac Reception of the Miracles of the Virgin - Minov, Sergey (Scrinium, 2024)
The article explores history of the reception of anti-Jewish hagiographical traditions of Western origin among Syriac Christians during the Islamic period by focusing on the textual tradition of the Miracles of the Virgin, a Western collection of Marian legends that was translated into Arabic during the thirteenth century and later on, during the nineteenth century, into Syriac. As an illustration, Syriac text and English translation of two relevant narratives from this work are offered: the Story of a young Frankish Jew and the Story of a Jewish boy.